2001
DOI: 10.1002/em.1025
|View full text |Cite
|
Sign up to set email alerts
|

Variation of micronucleated erythrocytes in peripheral blood of Sciurus aureogaster in relation to age: An increment of micronucleated polychromatic erythrocytes after the administration of colchicine

Abstract: In some species, in which the human is included, the influence of age in the variation in the number of micronucleated erythrocytes (MNE) is known. In the present work we show how the process of aging influences the number of spontaneous MNE in the gray squirrel (Sciurus aureogaster). Because of the difficulty of knowing the age of each animal, 69 animals were weighed at their arrival to the laboratory and at the start of sample taking, with the supposition that the heaviest animals were the oldest and those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 5 publications
0
16
0
4
Order By: Relevance
“…The use of non-human organisms to study genotoxic agents is rapidly increasing [Ruiz et al, 1992;Al-Sabti and Metcalfe, 1995;Burgeot et al, 1995;Choy et al, 1995;Jena and Bhunya, 1995;Ma et al, 1995;Zúñiga-González et al, 1998, 2001a, 2001b, and amphibians are of special interest in this regard due to their ecological niche [Jaylet et al, 1986;Krauter et al, 1987;Le et al, 1992;Rudek and Rozek, 1992;Fernandez and I'Haridon, 1994]. Urodela, which includes salamanders and newts, is one of the three surviving orders of the amphibian class.…”
Section: Introductionmentioning
confidence: 99%
“…The use of non-human organisms to study genotoxic agents is rapidly increasing [Ruiz et al, 1992;Al-Sabti and Metcalfe, 1995;Burgeot et al, 1995;Choy et al, 1995;Jena and Bhunya, 1995;Ma et al, 1995;Zúñiga-González et al, 1998, 2001a, 2001b, and amphibians are of special interest in this regard due to their ecological niche [Jaylet et al, 1986;Krauter et al, 1987;Le et al, 1992;Rudek and Rozek, 1992;Fernandez and I'Haridon, 1994]. Urodela, which includes salamanders and newts, is one of the three surviving orders of the amphibian class.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1996, our group has worked on identifying animal species with measurable frequencies of spontaneous micronucleated erythrocytes (MNEs) circulating in their peripheral blood [Zúñiga et al, 1996a;Zúñiga-González et al, 2000;Zúñiga-González et al, 2001a;Zúñiga-González et al, 2002], with the idea that analysis of MNE frequencies in these animals can be used as a biomonitor of exposure to genotoxic agents [Zúñiga-González et al, 1998;Zúñiga-González et al, 2001b;Gómez-Meda et al, 2004]. A highly proliferating tissue like blood is required to carry out this assay [Lähdetie, 1983;Shuilin and Baker, 1989;Schmezer et al, 1990;Torres-Bugarín et al, 1998;Zamora-Perez et al, 2004], and only a drop of blood is needed to measure micronucleus (MN) frequencies in peripheral blood, so that it is not necessary to kill the animal [Zúñiga-González et al, 1998;Zúñiga-González et al, 2001b].…”
Section: Introductionmentioning
confidence: 99%
“…Since the animals were not obtained from a well-controlled animal facility, there are likely to have been differences in the sex and age of the birds. Even though the birds were of a similar weight, they were not necessarily of similar age, and it has been observed that age can influence the capacity of animals to remove MNE from circulation (Zúñ iga-González et al , 2001a, 2001b.…”
Section: Resultsmentioning
confidence: 99%
“…We previously determined the frequency with which spontaneous micronucleated erythrocytes (MNE) appear in the species Aratinga canicularis (Zú ñiga- González et al , 2000). Interestingly, we observed a high frequency of BE (unpublished data), and, as a result, it is important to determine whether the presence of these abnormal erythrocytes may be inherent to this species or whether a genotoxic agent could have induced the appearance of such structures.…”
Section: Introductionmentioning
confidence: 99%